Determinants of Chronic Energy Deficiency in Pregnancy at Lebak Wangi Community Health Center, Banten, Indonesia - Rahmadhena, Melisa Putri; Astuti, Erlin Wibi (Journal of Maternal and Child Health, 2026)
Background: Malnutrition during pregnancy increases the risk of anemia, hypertension, miscarriage, fetal death, and causes low birthweight and fetal growth disorders that have a long-term impact on quality of life and health costs. Understanding and analyzing the problem of chronic energy deficiency in pregnant women based on comprehensive determinants is indispensable in order to design appropriate policies and treatment actions. This study aims to analyze the influence of the determinants of the incidence of chronic energy deficiency in pregnant women.Subjects and Method: This is a case control study conducted at the "Lebak Wangi" Health Center in Serang-Banten, Indonesia, in November 2025. The sample in this study was 105 pregnant women divided into 2 groups of cases, namely 53 pregnant women who suffered from chronic energy deficiency and a control group of 52 pregnant women with normal nutritional conditions. The exposure variable in this study is chronic energy deficiency). Independent variables were maternal age, gestational age, parity, education, economic status, haemoglobin level, and body mass index. The instrument research was master table. The analysis was carried out by multiple logistic regression.Results: Mothers with a lean body mass index are more likely to experience chronic energy deficiency up to 4.7 times more than mothers with a normal and statistically significant body mass index (aOR= 4.70; 95%CI= 0.34 to 0.83; p <0.001). Older gestational age has a 3.5 times smaller chance of chronic energy deficiency than younger gestational age and is statistically significant (aOR= -3.55;  95%CI= -2.61 to -0.75; p<0.001).Conclusion: The factors that have a significant influence in the case of SEZs are body mass index and gestational age.